Fetal deat h in multiple pregnancy - Lacunza Paredes, Rommel Omar (2015)
Single twin demise in the context of multiple pregnancy is rare but with severe consequences for the other twin. This event is more common in the first trimester and is clinically called vanishing twin; it may affect the normal development of the other twin. Understanding the complexity of vascular anastomosis in monochorionic gestation has helped to elucidate the pathophysiology of fetal death and brain damage, explained by exchange transfusion from one twin to the other, and determining the probability of death of the surviving fetus and neurological damage related to gestational age of occurrence, premature birth and monochorionicity. These cases require individual monitoring of the surviving fetus, neurosonography and magnetic resonance imaging.